Major Bricket and the circus corpse - Brett, Simon (Major Brickett mystery, 2025)
Meet Major Bricket, an infrequent resident of Highfield House in Stunston Peveril, Suffolk. In the past the Major's work assignments, frequently in foreign countries, have prevented him from spending much time there and, as a result, there is an air of mystery around him while everyone in the village speculates on the nature of his occupation. But now the Major has retired and has come home for good in his open-topped little red sports car... and what a homecoming it is, for lying spreadeagled on his lawn in the summer sunshine is the corpse of a clown. The circus is in Stunston Peveril for the annual village fair, yet none of their quota of clowns is missing - or at least, nobody is saying. Could the body be that of an unfortunate early guest at the village's highlight of the social calendar, the Fincham Abbey Costume Ball? Thankfully Major Bricket's past clandestine career means that he is now very well-placed to solve the mystery of the dead clown on his camomile lawn...